THE EFFECT OF KINESIO TAPPING TO REDUCE PAIN AND OEDEMA IN ANKLE SPRAIN PATIENTS: A CASE STUDY - Na'im, W. Azhar; Supriyadi, Arin; Fandrian, Ganang (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Sprain Ankleis a sports injury condition that causes problems in ligaments, muscles and joints. This condition causes instability in the ankle joint and causes pain and swelling on the injured side. Giving Kinesio Tapping can reduce pain levels, reduce swelling and can also provide stabilization of the ankle joint.Case Presentation:The patient came with difficulty walking, there was swelling, pain and the skin looked abnormal on the right ankle.Management and Outcome: In this case, the administration of kinesio tapping with the AET stretching technique of 30%-40% for two weeks with daily administration for 16 hours can reduce the level of pain as measured by a visual analogue scale and can reduce the size of swelling to its normal condition which is measured using a meterline. .Discussion:Using this technique for two weeks will help in the natural healing process. Proprioception will detect the location of joints and all moving extremities and help them recover to a normal position, in other studies showing that the application of tapping can improve proprioception by stimulating skin mechanoreceptors. The use of tapping is thought to reduce swelling by stimulating the drainage of edema in the interstitial spaces into less dense lymphatic channelsConclusion: In the cases and data described above, it has been proven that conventional therapy using kinesio tapping the acute eversion tapping technique in patients with ankle sprain injuries is able to reduce pain values measured using a visual analogue scale and the size of edema measured using a meterline.